IFNL4 Genotypes Predict Clearance of RNA Viruses in Rwandan Children With Upper Respiratory Tract Infections - Rugwizangoga, Belson; Andersson, Maria E.; Kabayiza, Jean-Claude; Nilsson, Malin S.; Ármannsdóttir, Brynja; Aurelius, Johan; Nilsson, Staffan; Hellstrand, Kristoffer; Lindh, Magnus; Martner, Anna (Frontiers in Cellular and Infection Microbiology, 2019)
Polymorphisms in the interferon lambda gene locus (IFNL) such as the IFNL4 genetic variants rs12979860 and rs368234815 are predictive of resolution of hepatitis C virus infection, but information about the impact of these variants in other infections is scarce. This study aimed at determining the potential impact of IFNL4 variation for the clearance of respiratory tract pathogens in Rwandan children (≤5 years old, n=480) seeking medical care for acute respiratory infections. Nasopharyngeal swabs were retrieved from all children at the first hospital referral and from 161 children at follow-up visits two weeks later. The swabs were analyzed for pathogens by real-time PCR and for host cell IFNL4 genotype at rs12979860 and rs368234815. Approximately 1/3 of the children were homozygous for the rs12979860 T allele and the rs368234815 ΔG allele, which are overrepresented in subjects of African descent. These IFNL4 variants were significantly associated with reduced clearance of RNA viruses. Our results suggest that IFNL4 genotypes that are common among subjects of African descent may determine the inefficacious clearance of RNA viruses from the respiratory tract.